Modeling and Simulating NOMA Performance for Next Generations (Journal of Engineering, 2023)
Non-orthogonal Multiple Access (NOMA) is a multiple-access technique allowing multiusers to share the same communication resources, increasing spectral efficiency and throughput. NOMA has been shown to provide significant performance gains over orthogonal multiple access (OMA) regarding spectral efficiency and throughput. In this paper, two scenarios of NOMA are analyzed and simulated, involving two users and multiple users (four users) to evaluate NOMA's performance. The simulated results indicate that the achievable sum rate for the two users’ scenarios is 16.7 (bps/Hz), while for the multi-users scenario is 20.69 (bps/Hz) at transmitted power of 25 dBm. The BER for two users’ scenarios is 0.004202 and 0.001564 for user 1 and user 2, respectively, while the BER for multi-users scenario are 0.001738, 0.000706, 0.000286, and 0.000028 for user 1, user 2, user 3, and user 4 respectively. In addition, this paper has compared NOMA with OMA in terms of achievable sum rate. The obtained results indicate that an improvement is achieved for two users NOMA (16.7 (bps/Hz)) compared with OMA (15.53(bps/Hz)), while for multi-users NOMA (20.69 (bps/Hz)) compared with OMA (15.79 (bps/Hz)) at transmitted power of 25 dBm.